Cocaine trafficking in Latin America: EU and US policy responses - Fukumi, Sayaka (Global security in a changing world)
The European Union and the United States have identified Latin American cocaine trafficking as a security threat, but their policy responses to it have differed. This book examines the ways in which the EU and the US have conceptualized this threat